Lsi1 modulates the antioxidant capacity of rice and protects against ultraviolet-B radiation. (January 2019) - Fang, Changxun; Li, Lanlan; Zhang, Pengli; Wang, Dahong; Yang, Luke; Reza, Boorboori Mohammad; Lin, Wenxiong
Highlights: Overexpression of Lsi 1 in rice enhances the antioxidant capacity and alleviates ultraviolet (UV)-B-induced damage. Differential miRNA expression is observed in WT and Lsi1 -OX and Lsi1 -RNAi transgenic rice exposed to UV-B irradiation. PAL2-2 expression is positively regulated by Lsi1 . Abstract: Silicon (Si) enhances the resistance of rice to biotic and abiotic stress. In rice, the accumulation of Si is controlled by the low silicon rice 1 ( Lsi1 ) gene; overexpression of Lsi1 ( Lsi1 -OX) increases Si uptake and accumulation, while the reverse is observed in Lsi1 -RNA interference ( Lsi1 -RNAi) transgenic rice. When the two transgenic rice lines and wild-type (WT) rice were exposed to ultraviolet (UV)-B radiation, the Lsi1 -OX or Lsi1 -RNAi rice showed differential microRNA (miRNA) expression, compared to WT rice. These miRNAs were predicted to target genes involved in light signal transduction and cell detoxification. The greatest capacities of ascorbate peroxidase, superoxide dismutase, peroxidase, and phenylalanine ammonia lyase (PAL) and highest contents of phenolics, flavonoids, and proline were found in Lsi1- OX rice, followed by WT rice and Lsi1 -RNAi transgenic rice. A further comparison of the transcript levels of individual PAL genes revealed that the expression of PAL2-2 ( Os02g0626400 ) was positively regulated by Lsi1 . Our results demonstrate that Lsi1 overexpression or interference causes changes in both miRNA expression and antioxidant capacity in rice, and therefore modulates rice tolerance to UV-B radiation. Furthermore, we demonstrated that PAL2-2 was positively regulated by Lsi1 during this process.